Spatio-temporal distribution of temperature, salinity and dissolved oxygen around the Costa Rica Thermal Dome. - Lizano, Omar G. (Revista de Biología Tropical, 2016)
The Costa Rica Thermal Dome (CRTD) is an oceanographic phenomenon in the Eastern Tropical Pacific (ETP). This is a region of very high biological productivity, resulting in high concentrations of phytoplankton, sea birds, and large pelagics, such as tunas, dolphins and whales. Few publications have looks at the station variability of the water column of the CRTD. Here, horizontal and vertical distribution of some oceanic parameters was analyzed to show the dynamics of ETP, its influence on the CRTD, climatic variations and relationships that justify their distributions. Climatological monthly mean data of Ocean Data View (ODV) from 1900 to 2009 were used to compile profiles of the water column’s temperature, salinity and dissolved oxygen, and their spatial distributions around the Costa Rica Thermal Dome (CRTD). Monthly variations of these parameters depend on the intensity and extent of ocean-meteorological phenomena in the Eastern Tropical Pacific (ETP), which are related to the north-south migration of Intertropical Convergence Zone (ITCZ). The monthly climatic variation of these variables is analyzed down to 200 m depth. Increased climate variability is found in the water column at stations north and east of the CRTD. The two stations north of the CRTD, closer to the coast, are the ones most affected by the wind in front of the Gulf of Papagayo and where the greatest monthly upwelling variation occurs in this region. The distribution and concentration of dissolved oxygen depends on the ocean-atmospheric dynamics. Oxygen is consumed by respiration and organic matter oxidation around CRTD. Moreover, this is one of the regions of the tropical oceans where an Oxygen Minimum Zone (OMZ) exist, which is related also to poor water circulation or lack ocean ventilation. Sources of dissolved oxygen are linked with sub-surface currents coming from the west and from the south of the geographic equator.